2022
DOI: 10.5194/cp-18-1601-2022
|View full text |Cite
|
Sign up to set email alerts
|

Was there a volcanic-induced long-lasting cooling over the Northern Hemisphere in the mid-6th–7th century?

Abstract: Abstract. The climate of the Northern Hemisphere (NH) in the mid-6th century was one of the coldest during the last 2 millennia based on multiple paleo-proxies. While the onset of this cold period can be clearly connected to the volcanic eruptions in 536 and 540 Common Era (CE), the duration, extent, and magnitude of the cold period are uncertain. Proxy data are sparse for the first millennium, which compounds the uncertainties of the reconstructions. To better understand the mechanisms of the prolonged coolin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…Most climate models confirm cooling effects following Northern Hemisphere volcanic eruptions, aligning with our dynamically downscaled iLOVECLIM model ensemble setup, which reveals surface cooling during the fimbulwinter in Scandinavia. Recent work by van Dijk et al (2022) utilizing the Max Planck Institute Earth System Model and identical PMIP4 volcanic forcing as our study, demonstrates significant cooling in mean Northern Hemisphere surface climate for up to two decades post the major eruptions of 536, 540, 574, and 626 AD. Earlier research on volcanic eruption effects within the last millenium, such as Timmreck et al (2009) and Guillet et al (2020), indicated a decade-long cooling period following exceptionally large eruptions.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Most climate models confirm cooling effects following Northern Hemisphere volcanic eruptions, aligning with our dynamically downscaled iLOVECLIM model ensemble setup, which reveals surface cooling during the fimbulwinter in Scandinavia. Recent work by van Dijk et al (2022) utilizing the Max Planck Institute Earth System Model and identical PMIP4 volcanic forcing as our study, demonstrates significant cooling in mean Northern Hemisphere surface climate for up to two decades post the major eruptions of 536, 540, 574, and 626 AD. Earlier research on volcanic eruption effects within the last millenium, such as Timmreck et al (2009) and Guillet et al (2020), indicated a decade-long cooling period following exceptionally large eruptions.…”
Section: Discussionsupporting
confidence: 60%
“…Archeological research into mid-sixth century Scandinavia increasingly links the periods' significant settlement abandonment, reorganization, and material transformation with a brief and abrupt cooling event which followed an explosive volcanic event between 536 and 540 AD (Axboe, 2001;Gräslund, 2007;Gräslund and Price, 2012;Guillet et al, 2020;Gundersen, 1970;Herschend, 2009;Löwenborg, 2023;Price and Gräslund, 2015;Sigl et al, 2013;Toohey et al, 2016;van Dijk et al, 2023;Zachrisson, 2011). The connection to volcanism is established through historical research on known volcanic eruptions before 630 AD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous modeling studies have found and confirmed that volcanic eruptions dominated hemispheric temperature changes over the second millennium of the CE (Brönnimann et al., 2019; Crowley, 2000; Hegerl et al., 2003; Schneider et al., 2009; Schurer et al., 2014). Furthermore, the prominent role of volcanic eruptions in the sixth‐century temperature was confirmed by climate model simulations (Toohey, Stevens, et al., 2016; van Dijk et al., 2022). However, the significant relationship between the solar activity and the NH temperature variability from the proxy data reconstructions (Connolly et al., 2021) is not supported by the climate model simulations over the second millennium of the CE (Schurer et al., 2014) and the Sun's total energy output measurement over the past 30 years (Foukal et al., 2006).…”
Section: Introductionmentioning
confidence: 78%
“…Three experiments from 1791 to 1830 are conducted in this study: Large-Only, Small-Included, and No-Volcano. The Large-Only experiment has the same setting as the MPI-ESM CMIP6/PMIP4 past2k simulation (van Dijk et al, 2022) and uses the EVA forcing for the aerosol optical properties from strong eruptions (Figure 1b). The Small-Included experiment changes the volcano forcing to eVolv2k plus D4i (Figure 1b), which includes the small-to-moderate volcanic eruptions as described in Section 2.2 and Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%